Integration of gender dimensions into water resources development and management: issues and information needs - Sagardoy J.A. (Integration of Gender Dimension in water management in the Mediterranean region : INGEDI Project, 2004)
The present paper aims at reviewing the role of women in the water resources development and management with particular attention to the Mediterranean Region. It is evident that considerable progress has been achieved in sensitizing the concerned institutions and the public in general for a greater participation of women in the water affairs. It has also become evident that sustainable water development and management and gender issues are mutually supporting and interdependent. There is evidence that the role that women and men play in water affairs are also different depending of the uses made and locations. This paper has reviewed such roles for the three main sectors, namely: Agriculture, Domestic and Sanitation and Rural Development. The analysis for each of these sectors has identified many issues and information gaps where action is needed to improve or reduce existing problems. A brief review is also made of the role of women role in the institutions of the sector and their access to planning and decision making.
Workshop on INtegration of GEnder DImension in Water Management in the Mediterranean Region, 2004/06/03-05, Bari (Italy)